Cosmos and Republic : Arendtian Explorations of the Loss and Recovery of Politics - Heuer, Wolfgang 1949- (Edition Politik, 2023)
Klappentext: In 20 essays inspired by Hannah Arendt's analysis of crisis-ridden modernity, Wolfgang R. Heuer addresses aspects of depoliticization and the loss of politics, and thus of freedom. The wide-ranging essays are grouped in five sections: When Politics Vanishes, The Call of Responsibility, Images and Emotions, Federations, and From Plurality to Cosmos. They lead to the insight that the crises of our time require a common change of perspective towards ecological and political sustainability, the unity of "Cosmos and Republic".